2009
DOI: 10.1210/jc.2009-0618
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin-Stimulating Hormone Receptor Gene Analysis in Pediatric Patients with Non-Autoimmune Subclinical Hypothyroidism

Abstract: To date, this study demonstrates the highest prevalence (29%) of TSHR gene mutations in children and adolescents with non-autoimmune subclinical hypothyroidism not selected by neonatal screening. Functional studies show that some mutations cause a slight inactivation of the TSHR. This reveals a possible limit of the in vitro study or of the knowledge of mechanisms involving TSHR, or that other candidate genes must be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 27 publications
5
41
0
1
Order By: Relevance
“…Nicolleti et al (9) reported similar findings among children with nonautoimmune SCH in Italy, but in that study, all of individuals were heterozygous, whereas in the present cohort, 16 subjects had either homozygous or compound heterozygous mutations. Contrary to the Italian cohort, which enrolled only SCH subjects, both SCH and CH children with RTSH characteristics were included in the current study.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Nicolleti et al (9) reported similar findings among children with nonautoimmune SCH in Italy, but in that study, all of individuals were heterozygous, whereas in the present cohort, 16 subjects had either homozygous or compound heterozygous mutations. Contrary to the Italian cohort, which enrolled only SCH subjects, both SCH and CH children with RTSH characteristics were included in the current study.…”
Section: Discussionsupporting
confidence: 49%
“…A prevalence of 4.3% biallelic TSHR mutations has been reported among Japanese infants with CH (8), whereas a high prevalence of 29% has been found among Italian children with nonautoimmune SCH (9).…”
mentioning
confidence: 97%
“…A prevalence of 4.3% biallelic TSHR mutations was found among 134 Japanese infants with CH (Narumi et al, 2009). Among 38 children with non-autoimmune subclinical hypothyroidism, 11 (29%) were carriers of TSHR mutations (Nicoletti et al, 2009). A prevalence of 12% TSHR mutations was shown in 42 subjects with non-autoimmune isolated hyperthyrotropinemia in Italy; all were with familial occurrence (Tonacchera et al, 2004).…”
Section: Prevalence Of Loss-of-function Mutationsmentioning
confidence: 95%
“…It was only in 1995 that the cause for RTSH syndrome in that case was shown to be a mutation in TSHR (Sunthornthepvarakul et al, 1995). Since the first report of CH caused by a TSHR mutation, several cases of loss-offunction mutations of TSHR have been reported: most are missense mutations, but deletions and insertions have been identified as well (see http: www.hgmd.cf.ac.uk/ac/ gene.php?gene=TSHR and OMIM#275200) (Abramowicz et al, 1997;Alberti et al, 2002;Biebermann et al, 1997Biebermann et al, , 2010Bretones et al, 2001;Camilot et al, 2005;Cangul et al, 2010;Clifton-Bligh et al, 1997;De Marco et al, 2009;de Roux et al, 1996;Fricke-Otto et al, 2005;Gagne et al, 1998;Grasberger et al, 2007;Jeziorowska et al, 2006;Jordan et al, 2003;Kanda et al, 2006;Nagashima et al, 2001;Narumi et al, 2009;Narumi et al, 2011;Park et al, 2004; …”
Section: Introductionmentioning
confidence: 99%
“…6 However, mutations in several proteins involved in TSH action including TSH receptor gene and mutations of dual oxidase 2 (DUOX2), phosphodiesterase 8B and thyroidperoxidase have also been demonstrated as causes of TSH elevation. [7][8][9][10] Although some clinicians consider SCH as a benign normal variation and thyroid hormone can be supplemented to lower the TSH levels and the exact cause of TSH elevation is unknown. But recent studies show higher mortality rates in young hypothyroid adults due to coronary heart disease and high TSH levels signify the importance of SCH and proving that SCH is not harmless.…”
Section: Introductionmentioning
confidence: 99%